Food selection by a mangrove crab: Temporal changes in fasted animals - Christofoletti, Ronaldo A. [UNESP]; Hattori, Gustavo Y. [UNESP]; Pinheiro, Marcelo A.A. [UNESP] (Springer Nature, 2013)
The feeding choices of the mangrove crab Ucides cordatus for various mangrove plant leaves (Avicennia schaueriana, Laguncularia racemosa, and Rhizophora mangle) at different ages (mature, senescent pre-abscission, and decomposing leaves) were examined. In a controlled experiment set in a mangrove area, we evaluated crab selection for different plant leaves by analyzing foraging rate (number of leaves with predation marks) and leaf consumption. Crabs were housed individually in plastic containers and after a 3-day fast supplied with leaf fragments every 24 h for 72 h. Uneaten leaves were removed before each new food offering. No food selection was observed in the first day, but after this period, senescent leaves, which have a high polyphenol content, were rejected. On the third day, an interactive effect between plant species and leaf age was shown to affect leaf selection, with mature leaves of A. schaueriana and L. racemosa being more selected than the other treatments. This observation was consistent across crab sexes and ages. Our results show that food selection by this mangrove crab changes through time in fasted animals, suggesting that this variable must be controlled in food preference studies. © 2012 Springer Science+Business Media B.V.
Keywords: Brazil; Experimental design; Foraging; Herbivory; Mangrove; Ucides; crab; experimental design; food preference; food selection; mangrove; phenol; senescence; Animalia; Avicennia; Decapoda (Crustacea); Laguncularia racemosa; Rhizophora mangle; Scylla; Ucides cordatus